REVELANDO RANGOS GEOGRÁFICOS ÓPTIMOS Y REQUERIMIENTOS ECOLÓGICOS DEL Harpia harpyja “ÁGUILA HARPÍA” Y Sarcoramphus papa “CÓNDOR DE LA SELVA” EN EL DEPARTAMENTO DE LORETO, PERÚ - HERNÁNDEZ MORA, Gonzalo (2025)
The use of computational tools combined with biological knowledge allows the identification of optimal areas of occupancy based on ecological requirements, which are key for species conservation. However, for many species, this baseline is lacking, especially in the department of Loreto, Peru. This study generated geographical distribution models for two Amazonian bird species: Harpia harpyja “harpy Eagle” and Sarcoramphus papa “King Vulture”. Using a combination of geographic occurrence data and bioclimatic variables, the modeling was conducted with the Maxent algorithm. Our models indicated that for H. harpyja, the optimal conditions of occurrence were located in the north and east of the department, in the provinces of Putumayo, Mariscal Ramón Castilla, and Maynas, with the most important bioclimatic variables being the mean diurnal temperature range and annual precipitation. For S. papa, the optimal areas were discontinuous, mainly in the north, southeast, and south, particularly in the provinces of Requena and Mariscal Ramón Castilla, with the most important bioclimatic variables being the mean annual temperature and annual temperature range. Our results, together with geographic information and field data collection, can be useful in species conservation efforts, sampling site prioritization, and the creation of ecological corridors.